Competition and Regulation in the Early History of the London Gas Industry, 1800–1830. (July 2014) - Tomory, Leslie
<x content-type="archive" xml:space="preserve">Abstract</x> The British gas industry was first formed in the period 1800–1830, and it was centred in London. During this time, questions were repeatedly raised about the safety of the new technology, particularly in regard to explosions. Over time, this led to repeated discussions about whether the industry should be regulated by the government for safety reasons. These discussions first took place in 1814, but eventually a bill to regulate the gas industry was introduced in Parliament in 1823, although it was ultimately rejected. This timeline is notable because these proposals to regulate the gas industry came before the reform of the state which began in the 1830s, and saw the introduction of the first government measures to regulate the internal affairs of business.